Kebutuhan Pasien Akan Pelayanan Pastoral Bagi Orang Sakit - Maria Margaretha Basela Wokal; Nikolaus Anggal (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2019)
This study aims to know the needs of patients, and pastoral actions in the hospital and to analyze whether pastoral actions have answered the patient’s needs . The method used in this study is qualitative descriptive. Data collection techniques used are interviews, observation and documentation. The observation phase was carried out before interviewing patients. After carrying out observations the researchers conducted interviews with pastoral care officer and Catholic patients who were hospitalized at the Hospital. The last step is documentation. The results of this study show that each patient has different needs according to the pain suffered, from physiological needs, security and safety, social and self-esteem. Even though only one companion carries out pastoral care, she was able to meet the needs of patients by carrying out the functions of pastoral care namely: guiding, reconciling, sustaining and healing.